JINTRAC integrated simulations of ITER scenarios including fuelling and divertor power flux control for H, He and DT plasmas. (1st December 2022) - Militello Asp, E.; Corrigan, G.; da Silva Aresta Belo, P.; Garzotti, L.; Harting, D.M.; Köchl, F.; Parail, V.; Cavinato, M.; Loarte, A.; Romanelli, M.; Sartori, R.
Abstract: We have modelled self-consistently how to most efficiently fuel ITER hydrogen (H), helium (He) and deuterium–tritium (DT) plasmas with gas and/or pellets with the integrated core and 2D SOL/divertor suite of codes JINTRAC. This paper presents the first overview of full integrated simulations from core to divertor of ITER scenarios following their evolution from X -point formation, through L-mode, L–H transition, steady-state H-mode, H–L transition and current ramp-down. Our simulations respect all ITER operational limits, maintaining the target power loads below 10 MW m −2 by timely gas fuelling or Ne seeding. For the pre-fusion plasma operation (PFPO) phase our aim was to develop robust scenarios and our simulations show that commissioning and operation of the ITER neutral beam (NB) to full power should be possible in 15 MA/5.3 T L-mode H plasmas with pellet fuelling and 20 MW of ECRH. For He plasmas gas fuelling alone allows access to H-mode at 7.5 MA/2.65 T with 53–73 MW of additional heating, since after application of NB and during the L–H transition, the modelled density build-up quickly reduces the NB shine-through losses to acceptable levels. This should allow the characterisation of ITER H-mode plasmas and the demonstration of ELM control schemes in PFPO-2. In ITER DT plasmas we varied the fuelling and heating schemes to achieve a target fusion gain of Q = 10 and to exit the plasma from such conditions with acceptable divertor loads. The use of pellets in DT can provide a faster increase of the density in L-modes, but it is not essential for unrestricted NB operation due to the lower shine-through losses compared to H. During the H–L transition and current ramp-down, gas fuelling and Ne seeding are required to keep the divertor power loads under the engineering limits but accurate control over radiation is crucial to prevent the plasma becoming thermally unstable.